Genome-based analysis of the genetic pattern of black sheep in Qira sheep - Wen Zhou; Xiaopeng Li; Xuechen Zhang; Lijun Zhu; Yuwei Peng; Cheng-long Zhang; Zhipeng Han; Ruizhi Yang; Xinyu Bai; Quanfeng Wang; Yuejun Zhao; Shudong Liu (BMC Genomics)
Abstract Objective Black wool can effectively prevent sheep from DNA damage as well as fungal infection, and can improve reproductive performance. In order to explore the candidate genes related to black wool formation in Qira sheep. Methods We selected 123 adult healthy ewes with different coat colors in Qira sheep groups (black (B), brown (Y) and grey (G)) and extracted DNA from their venous blood to obtain Illumina Ovine SNP 50K chip data. Subsequently, our PCA, NJ-tree, and Admixture population structure analyses of the 3 wool color Qira sheep populations showed that the 3 middle wool color populations exhibited the same genetic traits. Fst, xp-EHH, iHS, and π were detected for selection signals, and the 5% SNPs loci positively selected from the analyses were annotated based on SheepOar_v4.0. The region of exon 1 of the TYRP1 gene was further screened, amplified and sequenced through the DNA of the Qira sheep and associated with goodness-of-fit using the chi-square test. Results The results showed that 71 SNPs associated with black wool traits, among which TYRP1, PARD3 and CDH2 genes were strongly associated with black wool production. Three mutations were detected in the exon 1 region of the TYRP1 gene that were significantly associated with coat color variation inQira sheep (2:81,183,168, 2:81,183,281 and 2:81,183,284). Conclusion In this paper, Qira sheep could not differentiate the genetic structure of this population by wool color, and obtained 71 SNPs related to black wool. Detection of mutation sites on the TYRP1 gene affecting hair color change provides a basis for black sheep line selection as well as breed conservation.